2016
DOI: 10.1186/s40608-016-0091-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with BMI, underweight, overweight, and obesity among adults in a population of rural south India: a cross-sectional study

Abstract: BackgroundOverweight, obesity, and related chronic diseases are becoming serious public health concerns in rural areas of India. Compounded with the existing issue of underweight, such concerns expose the double burden of disease and may put stress on rural healthcare. The purpose of this article was to present the prevalence and factors associated with underweight, overweight, and obesity in an area of rural south India.MethodsDuring 2013 and 2014, a random sample of adults aged 20–80 years were selected for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
63
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 73 publications
24
63
1
Order By: Relevance
“…Despite the controversy regarding the use of BMI [47] to predict disease, BMI remains the most commonly used marker of whole body obesity. By 2014, it was estimated that approximately a billion adults were overweight and that 600 million were obese worldwide [8]. Within SSA, the prevalence of obesity has been increasing over the past 30 years with regional disparities [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the controversy regarding the use of BMI [47] to predict disease, BMI remains the most commonly used marker of whole body obesity. By 2014, it was estimated that approximately a billion adults were overweight and that 600 million were obese worldwide [8]. Within SSA, the prevalence of obesity has been increasing over the past 30 years with regional disparities [9].…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Tables 4 to 6, gender, VO2peak, overweightedness and physical activity level were not predictors of enjoyment in PE, when the effects of the other possible predictors were controlled for. The absence of such group differences in enjoyment among others are surprising, in a positive way, especially because previous research indicate such differences (Biddle et al, 2011;Bjerke et al, 2016;Flagestad, 1996;Flagestad and Skisland, 2002;Kjønniksen et al, 2009;Larsson and Redelius, 2008;Latty et al, 2007;Little et al,, 2016;Säfvenbom et al, 2014;Wabakken, 2010). As earlier pointed out, the fostering of an autonomy supportive environment by PE teachers in high school may help explain the lack of group differences at high school.…”
Section: Factors That Predict Very Good Enjoyment In Pementioning
confidence: 99%
“…[13,16] Factors associated with obesity included: sex, leisure-time, physical exercise, (and educational level appear to influence obesity) low physical activity, high wealth index, no livestock, low animal fat consumption, high n-6 polyunsaturated fat consumption, television ownership, time spent watching television, low rurality index, high caste, older age, rural living, current smoking, lower systolic pressure, urbanization, higher systolic pressure, and diabetes. [10,13,17,18] On the other hand, studies have shown that underweight was associated with low wealth index, high rurality index, low intake of n-6 PUFAs and less urbanization. [10,18] There is a paucity of studies on the associated factors of underweight, overweight and obesity in the general out patients in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…[10,13,17,18] On the other hand, studies have shown that underweight was associated with low wealth index, high rurality index, low intake of n-6 PUFAs and less urbanization. [10,18] There is a paucity of studies on the associated factors of underweight, overweight and obesity in the general out patients in Nigeria. This has prompted us to evaluate BMI and the factors which might be associated with underweight and obesity in this group of people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation